SUCCESSFUL AGEING FROM THE PERSPECTIVE OF YOUNG ADULTS IN POLAND - Kozerska, Agnieszka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
On the basis of the theoretical and empirical analyses published in the scientific literature, it can be stated that the concept of successful ageing presented in educational discourses is understood differently by authors and it is focused primarily on three issues related to 1/ spirituality, 2/ well-being, 3/ a sense of community. The article discusses research results aimed at comparing ways of understanding successful ageing in the scientific literature with ways of defining this term by young adults in Poland. The survey participants are pedagogy students. The article attempts to answer the following questions: 1/ How do young adults in Poland understand the concept of successful ageing?, 2/ To what extent do the ways of understanding this concept, which have been distinguished based on the analysis of empirical data, coincide with a typology created based on a review literature.Data analysis (cluster analysis) enables to distinguish two types of successful ageing understood as a link between transcendence and generativity. The third type consists of elements of Rowe and Kahn model which are supplemented with good family relations.